Effect of the Replacement of Cement by Fly Ash and Calcined Clay on the Mechanical-Physical Properties of Conventional Mortar - Saravia, Aracelly (2025)
This article explored the effects of replacing Portland cement with fly ash and calcined clay on the strength and durability of conventional mortar, focusing on improving its mechanical properties and reducing the carbon footprint generated by the construction industry. Tests were conducted on samples with 20% and 55% cement replacements ratios, evaluating parameters such as compressive strength, flexural strength, and porosity. The results indicated that mortars with cement replacements outperformed the control mortar in terms of strength and compaction. At 28 days, the mortar with a 20% replacement achieved a compressive strength of 24.67 MPa, surpassing the standard design. Lower porosity was also observed in mortars with replacements, contributing to greater durability and resistance to water absorption. This study concluded that using fly ash and calcined clay as a partial replacement for cement was viable for structural applications, particularly in seismic zones, due to improved cohesion and reduced formation of voids in the mix, enhancing its mechanical performance and reducing its environmental impact. ©